2020
DOI: 10.1080/17434440.2020.1789456
|View full text |Cite
|
Sign up to set email alerts
|

How valvular calcification can affect the outcomes of transcatheter aortic valve implantation

Abstract: Introduction: In transcatheter aortic valve implantation (TAVI), assessment of aortic valve calcification is not as standardized as aortic annulus measurement. Aortic valve calcification is important for stable anchoring of the prosthesis to the aortic annulus. However, excessive aortic valve calcification is related to procedural complications. Areas covered: This review covers the methods to assess aortic valve calcification and the implications of aortic valve calcium burden for TAVI outcomes. We performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…Although sizing error is one of the most common reasons for valve migration in TAVI, 19 and theoretically all patients receiving TAVI in this series were exposed to sizing error due to significant valve undersizing, there is also agreement on importance of amount and distribution of aortic valve complex calcification on clinical efficacy in TAVI. While severe calcification is traditionally considered to be a predictor for significant postoperative PVL and PPI, 20,21 it is also well recognized from TAVI for pure aortic regurgitation that patients with no to mild calcifications of the aortic valve complex may still be safely treated if oversizing of THV is planned to avoid valve embolization. 22,23 Therefore, the herein presented results suggest that decision making regarding overfilling strategies in BE THV are a balance between risk of valve embolization and risk of residual hidden confounders may apply.…”
Section: Discussionmentioning
confidence: 99%
“…Although sizing error is one of the most common reasons for valve migration in TAVI, 19 and theoretically all patients receiving TAVI in this series were exposed to sizing error due to significant valve undersizing, there is also agreement on importance of amount and distribution of aortic valve complex calcification on clinical efficacy in TAVI. While severe calcification is traditionally considered to be a predictor for significant postoperative PVL and PPI, 20,21 it is also well recognized from TAVI for pure aortic regurgitation that patients with no to mild calcifications of the aortic valve complex may still be safely treated if oversizing of THV is planned to avoid valve embolization. 22,23 Therefore, the herein presented results suggest that decision making regarding overfilling strategies in BE THV are a balance between risk of valve embolization and risk of residual hidden confounders may apply.…”
Section: Discussionmentioning
confidence: 99%
“…Because unremoved aortic valve calcification in TAVR is the characteristic of TAVR in contrast to SAVR, studies on the clinical effect of aortic valve calcium extent have been actively conducted. The aortic valve calcium extent is known to affect various poor outcome after TAVR, such as paravalvular leakage, stoke, coronary ostium occlusion and conduction abnormality ( 35 ). It is meaningful because this study firstly revealed the direct relation of aortic valve calcium extent with leaflet thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The location of calcium predicts complications: calcification of the raphe(s) affects device expansion, and increases the risks of regurgitation, misplacement, and pacemaker requirement; calcium at the commissures may cause perforation; calcium at the tip of a leaflet risks coronary obstruction (although in most BAV patients spacious sinuses often protect against coronary occlusion). In addition, severe calcification in BAV with a tapered configuration confers a risk of Valsalva rupture [ 10 ].…”
Section: Introductionmentioning
confidence: 99%